Respuestas

2014-01-25T14:41:55+01:00

x^2 + 2x + 2 > x + 6
Preparando la ecuación cuadrática
x^2 + x - 4 > 0
Resolviendo la ecuación:
           x1 = [- 1 - (raiz 17)]/2
           x2 = [- 1 + (razi 17)]/2
Del correspondiente estudio de signos:
                x > [- 1 - (raiz 17)]/2   RESULTADO FINAL

x +4 < 6x - x^2 - 2
Preparando la ecuación cuadrática
x^2 - 5x + 6 < 0
Resolviendo la ecuación
            x1 = 2
            x2 = 3
Del correspondiente estudio de signos:
            x < 3   RESULTADO FINAL